Aplikasi Pembelajaran Berbasis Mobile Untuk Tuna Aksara - Padli Nasution, Muhammad Irwan; Andriana, Septiana Dewi (Department of Informatics Engineering, 2016)
Abstract - Learning is a process of transformation that is initially not knowing to knowing. Has developed a lot of learning strategies from simple to more complex models even complicated and required a lot of tools in its application. Literacy is a basic of knowledge for humans. They can read by improving their quality, which leads to the high intellect of a person. Especially at this time humanity has entered the information age. The phenomenon of globalization is happening now accelerating so quickly, as the impact of application of Hi-tech society (high-tech society), which causes humans followed on interaction patterns very quickly. Using Information and Communication Technology (ICT) could be developed multimedia teaching materials with the concept of learning by playing fun and implemented on a mobile based learning applications. The use of mobile devices that is easy and flexibility is very useful to support the learning process for the illiterate.